2021
DOI: 10.1007/s10681-021-02798-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of improved cassava genotypes for yield and related traits for a better breeding strategy under different agroecologies in Nigeria

Abstract: This study aimed at determining shoot and root characteristics of cassava as affected by root yield and the influence of soil moisture on vegetative growth and yield. Thirty cassava genotypes were evaluated for morphological and physiological characterization in three locations in Nigeria: Ibadan, Mokwa and Zaria. Randomized complete block design was used with four replicates. Studies on the pasting properties of the genotypes were also carried out. Data were collected on plant height, stem girth, stay-green a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…On the other hand, the results of the effect of plant spacing on stem girth during this study showed a statistically significant between the treatments registering the highest maximum stem girth of 38.1 cm in treatment (T1) with spacing (50x50 cm). These results coincided with the finding of Adetoro et al, [14] reporting the highest stem girth in plants with the widest spacing and it was gradually decreased with decreasing plant spacing where the lowest was recorded on the closest spacing.…”
Section: Plant Height Stem Girth and Number Of Leavessupporting
confidence: 92%
“…On the other hand, the results of the effect of plant spacing on stem girth during this study showed a statistically significant between the treatments registering the highest maximum stem girth of 38.1 cm in treatment (T1) with spacing (50x50 cm). These results coincided with the finding of Adetoro et al, [14] reporting the highest stem girth in plants with the widest spacing and it was gradually decreased with decreasing plant spacing where the lowest was recorded on the closest spacing.…”
Section: Plant Height Stem Girth and Number Of Leavessupporting
confidence: 92%
“…According to Phoncharoen et al [9], different planting locations would produce different amounts of cassava production. Genotypes differed significantly within and between locations for shoot and root characteristics [10]. Sundari and Yulifianti [11] reported that the interaction between genotype and planting location had a significant effect on the character of cassava production and observed cassava starch content.…”
Section: Resultsmentioning
confidence: 99%
“…More complex approaches utilizing wholegenome single-nucleotide polymorphisms (SNPs) like genotyping by sequencing and genome-wide association mapping (dos Santos Silva et al, 2021) have also been harnessed. The major traits targeted in breeding for drought tolerance include enhanced leaf retention (stay green) (Adetoro et al, 2021), root and shoot storage yields, dry matter and starch content (Oliveira et al, 2015).…”
Section: Enhancing Drought Resiliencementioning
confidence: 99%